1985
DOI: 10.2307/1541309
|View full text |Cite
|
Sign up to set email alerts
|

ADHESIVE INTERACTIONS BETWEEN THE TUBE FEET OF A STARFISH,LEPTASTERIAS HEXACTIS, AND SUBSTRATA

Abstract: The tube feet of Leptasterias hexactis adhere to and release from substrata by chemical interactions. In our laboratory these podia adhered to substrata coated with the ubiquetous anionic saccharide films produced by marine bacteria. Podia also attached to moderately anionic glass, but not to uncharged surfaces. The adhesive epithelia of tube feet labeled heavily with ruthenium red, indicating they were anionic. Tube feet secreted footprint films that bound crystal violet, a cationic dye. Trypsin removed the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 25 publications
3
37
1
Order By: Relevance
“…Temporary adhesives for example have been examined only in two taxa, monogenean flatworms and sea stars, in terms of their ultrastructure (Hamwood et al, 2002;Flammang, 2006). In the latter, the adhesive material was described using light microscopy (LM) (Thomas and Hermans, 1985), SEM (Flammang et al, 1994(Flammang et al, , 1998 and TEM (Flammang et al, 1994), and always appeared as a heterogeneous, sponge-like material. This material is secreted by specialized hydraulic organs, the tube feet, which consist of a proximal extensible stem and a distal flattened disc (see Flammang, 1996, for review).…”
Section: Introductionmentioning
confidence: 99%
“…Temporary adhesives for example have been examined only in two taxa, monogenean flatworms and sea stars, in terms of their ultrastructure (Hamwood et al, 2002;Flammang, 2006). In the latter, the adhesive material was described using light microscopy (LM) (Thomas and Hermans, 1985), SEM (Flammang et al, 1994(Flammang et al, , 1998 and TEM (Flammang et al, 1994), and always appeared as a heterogeneous, sponge-like material. This material is secreted by specialized hydraulic organs, the tube feet, which consist of a proximal extensible stem and a distal flattened disc (see Flammang, 1996, for review).…”
Section: Introductionmentioning
confidence: 99%
“…To assess risk of dislodgment of an organism, the nature of the water flow, the resultant hydrodynamic forces and the organism's ability to resist those forces must be characterized (Lau & Martinez 2003). Sea urchins are common inhabitants of the rocky intertidal environment, being able to withstand mechanical stress by a combination of strong adhesion to the substratum and ability to move, through voluntary attachment -detachment cycles of their tube feet (Thomas & Hermans 1985, Flammang 1996, Flammang et al 2005. Attachment is achieved by means of a multitude of independent adhesive organs, the tube feet.…”
Section: Introductionmentioning
confidence: 99%
“…3B). In previous studies, the disruption of footprints from the substratum by trypsin treatment demonstrated the crucial role of proteins for adhesion and cohesion (5,18). In the species Asterias rubens, proteins are the main organic components of the adhesive material (20% of the footprint dry weight compared with 8% for carbohydrates and 6% for lipids) (14,16).…”
mentioning
confidence: 97%